Management of Canine Leishmaniasis and the Treatment Trends of Veterinarians in Aegean Region of Türkiye: A Questionnaire-based Survey - Metin Pekağırbaş; Mehmet Karakuş; Elif Dönmez; Hüseyin Gökhan Özdemir; Yusuf Özbel; Seray Töz (Türkiye Parazitoloji Dergisi)
Objective: Canine leishmaniasis (CanL) is an important veterinary and public health problem in Mediterranean countries. Although CanL and vector sandflies are widespread in the study area, there are no standardized diagnostic and treatment methods followed by private clinics. This study aimed to survey (i) the treatment, diagnosis, and control measures preferred by veterinarians, (ii) compare the differences in the first-step diagnostic tests applied, and (iii) identify differences in the guidance for CanL. Methods: This study was conducted between August 2017 and 2019, and an accessible weblink was distributed to veterinary clinics that were registered with the Veterinary Affairs of İzmir. The questionnaire was prepared by following published guidelines and several CanL guidelines and comprised 13 questions. A total of 103 veterinarians voluntarily participated in the study and completed the questionnaire. Results: Most of the clinicians (n=99; 96.1%) reported that localized alopecia was one of the most common clinical findings in the suspicion of CanL, while only four clinician did not consider this finding in the suspicion of CanL. According to the answers received, 41 clinician (39.8%) frequently observed this finding in CanL-suspected cases, 49 clinician (47.6%) observed it occasionally, and nine clinician (8.7%) rarely observed this finding. The findings of the study indicate that a minority of clinicians employ advanced diagnostic techniques. Conclusion: The results demonstrate that veterinarians play a unifying role in the fight against CanL. However, the preference for less advanced diagnostic methods over those employed by their European counterparts may result in insufficient detection of particularly asymptomatic patients. It is therefore necessary to validate rapid diagnostic tests, which are the most used method for diagnosing the disease. Furthermore, there is a need to increase awareness of the disease among patient owners and veterinarians in regions where it is endemic, and to recognise it as a notifiable disease in Türkiye.